BANDUNG Contyroversies and consensus in obstetrics & gynecology / editor, Tono Djuwantono, Wiryawan Permadi, Mulyanusa A. Ritonga. - Tono Djuwantono; Wiryawan Permadi; Mulyanusa A. Ritonga (Sagung Seto, 2011)
xviii, 392 hlm. : ilus. ; 24 cm (3 eks.)